The Students’ Ability in Using Asking and Giving Opinion Expression to Develop Speaking Skill at The Ninth Grade Students of MTs PSM Suka Agung Buay Bahuga Way Kanan - Niswatun, Niswatun; Franzhardi, Didi; Jelita (English Education Program, Education Faculty, Universitas Nurul Huda, 2022)
The title of thesis is: The Students’ Ability in Using Asking and Giving Opinion Expression to Develop Speaking Skill at the Ninth Grade Students of MTs PSM Suka Agung Buay Bahuga Way Kanan. The main problem of this study is “Is it significantly effective of Using Asking and Giving Opinion Expression to Teach Speaking Skill at the Ninth Grade Students of MTs PSM Suka Agung Buay Bahuga Way Kanan?”. The main objective of this study that to know whether or not effective of the Students’ using asking and giving opinion expression to teach speaking skill at the ninth grade students of MTs PSM Suka Agung Buay Bahuga Way Kanan. In this study, experimental method was used. The population was all at the Ninth Grade Students of MTs PSM Suka Agung Buay Bahuga Way Kanan. The total number of population was 122 students. The sample was 60 students taken through cluster simple random sampling method, consisting of 30 students of experiment group and 30 students of control group. Based on the criteria of testing the hypothesis, the alternative hypothesis (Ha) was tested through t-test table. Since the sample of the researcher was 60 students. Therefore, to accept the alternative hypothesis with 5% significance, the value should exceed 2.750 with df = (n1+n2 - 2) it was mean that (30+30 - 2) = 58 students. The result of matched t-test calculated 1.671 lower that the result of matched t-test that has value 2.75. It means that Ho was rejected and Ha was accepted. In the other word, the result of the study showed that it was effective teaching Speaking Skill by using Asking and Giving Opinion Expression at Ninth Grade Students of MTs PSM Suka Agung Buay Bahuga Way Kanan.